Analisis Proses Morfologis dalam Naskah Latoa: Afiksasi, Reduplikasi, dan Komposisi Bahasa Bugis - Hasan, Nur Fauziah; Hajrah, Hajrah; Asia M (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to describe the form and meaning of affixation, reduplication, and composition in the Latoa Manuscript by Prof. Dr. Mattulada. This study uses a qualitative descriptive method with a reading and recording technique as a data collection technique, which is then analyzed through the stages of identification, classification, analysis, and description. The results show that the process of affixation in the manuscript includes the use of the prefixes maK-, paK-, and teK- , the suffix -na, and the ma-, -pi suffix which not only form a new word, but also expand the lexical meaning and show changes in sound through phonological processes such as regressive assimilation. Reduplication is found in full and partial forms, both stand-alone and accompanied by affixes such as maccule-cule, with the function of reinforcing the meaning of intensity, repetition of actions as in the word manu-manu, and expressive emphasis on paccai-caireng. The composition in this manuscript reflects the formation of a new meaning that is idiomatic through the combination of two lexemes that form a unity of meaning that can be found in the word ulu ada. These findings show that morphological processes in the Bugis language have an important role in shaping grammatical structure and contextual conveyance of meaning. This research is expected to enrich the study, especially the morphology of regional languages, as well as support efforts to preserve Bugis cultural heritage through understanding the structure of language in traditional literary works.